Preparação e caracterização eletroquímica do eletrodo SiO2/MPTS/nAu para o estudo eletrocatalítico da reação de oxidação do ácido ascórbico - Morais, Andréia De (2010)
A 3-mercaptopropyl functionalized silica network was synthesized using the sol-gel process. Gold nanoparticles (nAu) were immobilized on the material at the synthesis, by adding a suspension of these previously prepared particles to the reaction mixture. The Transmission Electron Microscopy and ultraviolet-visible Spectrophotometry were used to obtain information about the nAu average size. The characterization of the obtained material was performed by Infrared Spectrometry, Solid State Nuclear Magnetic Resonance and Diffuse Reflectance Spectroscopy. The electrochemical behavior of the SiO2/MPTS/nAu electrode was studied using Cyclic Voltammetry and Electrochemical Impedance Spectroscopy in the presence of a hexacyanoferrate probe molecule. The presence of nAu in the functionalized silica network changes the electrochemical characteristics of the material, favoring the electron transfer process of this complex ion. The SiO2/MPTS/nAu electrode was proven to be an efficient tool in the determination of ascorbic acid (AA) using Cyclic Voltammetry, Chronoamperometry and Square Wave Voltammetry techniques. The presence of dopamine (DA) and uric acid (UA) on AA electrochemical oxidation were also studied. With the nAu on the electrode, an increase in the peak current that was related to the redox process of the AA, DA and UA was observed, probably due to the nAu adsorbed on the functionalized silica network. The separation of the anodic peak potentials between DA/AA and UA/AA were 310 and 442 mV, respectively. The results obtained show that the SiO2/MPTS/nAu electrode can be used in the simultaneous determination of AA, DA and UA.